Rock River Stormwater Group: 2013 stormwater related perceptions, knowledge and practices survey report - Hadley, Shelly; Trechter, David (My University, 2014)
The goals of the survey were to provide the Rock River Stormwater Group (RRSG) with information to help local efforts to improve area lakes and streams. Input was sought from households in the Rock River Stormwater Group area consisting of 9 municipalities within South Central Wisconsin. Involved municipalities are the cities of Janesville, Beloit, Watertown, Beaver Dam, Whitewater, Ft. Atkinson, Jefferson, Milton, and the town of Beloit.
ii + 38 p.
Keywords: Walworth County; Rock County; Stormwater infiltration--Wisconsin; Water quality--Wisconsin; Water--Pollution--Wisconsin; Beloit (Wis.); Jefferson (Wis.); Water quality management--Wisconsin; Storm sewers--Wisconsin; Water supply--Wisconsin; Janesville (Wis.); Urban runoff--Environmental aspects--Wisconsin; Dodge County; Jefferson County; Watertown (Wis.); Beaver Dam (Wis.); Whitewater (Wis.); Fort Atkinson (Wis.); Milton (Wis.); Beloit (Wis. : Town)